Childhood Traumas versus Marital Dilemmas: A Feminine Psychological Analysis of Paula Hawkins’ The Girl on the Train - Bashir, Saima; Fatima, Bismia (Annals of Human and Social Sciences, 2024)
The article delves into the intricate exploration of marital conflicts within Paula Hawkins’ psychological thriller The Girl on the Train (2015) by utilizing Karen Horney’s theory of Feminine Psychology as a guiding framework. The psychological trauma of Rachel Watson, the female protagonist, becomes pivotal in unraveling the complexities of her failed marriage. The qualitative research method of research is used to dissect the traumatic events leading to the dissolution of the marriage and the subsequent aftermath. Through the lens of Horney’s theory which challenges traditional Freudian perspectives on female psychology, the research sheds light on the profound effects of societal gender biases and objectification. By exploring how Rachel Watson copes with the aftermath of her failed marriage, the study provides insight into the individual’s journey of self-discovery and resilience, and contributes to a deeper understanding of the female psyche, marriage dynamics, and societal influences on woman’s role in a relationship.